Ca(2+) current facilitation is CaMKII-dependent and has arrhythmogenic consequences - Bers, Donald M. (Frontiers Media S.A., 2014)
The cardiac voltage gated Ca(2+) current (I(Ca)) is critical to the electrophysiological properties, excitation-contraction coupling, mitochondrial energetics, and transcriptional regulation in heart. Thus, it is not surprising that cardiac I(Ca) is regulated by numerous pathways. This review will focus on changes in I(Ca) that occur during the cardiac action potential (AP), with particular attention to Ca(2+)-dependent inactivation (CDI), Ca(2+)-dependent facilitation (CDF) and how calmodulin (CaM) and Ca(2+)-CaM dependent protein kinase (CaMKII) participate in the regulation of Ca(2+) current during the cardiac AP. CDI depends on CaM pre-bound to the C-terminal of the L-type Ca(2+) channel, such that Ca(2+) influx and Ca(2+) released from the sarcoplasmic reticulum bind to that CaM and cause CDI. In cardiac myocytes CDI normally pre-dominates over voltage-dependent inactivation. The decrease in I(Ca) via CDI provides direct negative feedback on the overall Ca(2+) influx during a single beat, when myocyte Ca(2+) loading is high. CDF builds up over several beats, depends on CaMKII-dependent Ca(2+) channel phosphorylation, and results in a staircase of increasing I(Ca) peak, with progressively slower inactivation. CDF and CDI co-exist and in combination may fine-tune the I(Ca) waveform during the cardiac AP. CDF may partially compensate for the tendency for Ca(2+) channel availability to decrease at higher heart rates because of accumulating inactivation. CDF may also allow some reactivation of I(Ca) during long duration cardiac APs, and contribute to early afterdepolarizations, a form of triggered arrhythmias.